Case Report: Mycobacterium kansasii causing infective endocarditis explored by metagenomic next-generation sequencing - Yang, Liuqing; Peng, Ling; Yuan, Ke; Cai, Kanru; Feng, Cheng; Yang, Gendong; Wang, Shunyao; Zhu, Xiuyun; Zhang, Jieyun; Wang, Fuxiang; Lu, Hongzhou (Frontiers in Cellular and Infection Microbiology, 2023)
In this report, we describe the first case of infective endocarditis caused by Mycobacterium kansasii in a 45-year-old male patient who presented with a 10-day fever and decompensated cirrhosis. Despite negative results in blood culture and pathology, we employed metagenomic next-generation sequencing (mNGS) to analyze the genome sequences of both the host and microbe. The copy number variation (CNV) indicated a high risk of liver disease in the patient, which correlated with biochemical examination findings. Notably, M. kansasii sequences were detected in peripheral blood samples and confirmed through Sanger sequencing. Unfortunately, the patient’s condition deteriorated, leading to his demise prior to heart surgery. Nevertheless, we propose that mNGS could be a novel approach for diagnosing M. kansasii infection, particularly in cases where blood culture and pathology results are unavailable. It is important to consider M. kansasii infection as a potential cause of endocarditis and initiate appropriate anti-infection treatment.